Effect of Roles playing method In Achievement of Physics subject for second–grade Intermediate female students and their attitude towards physics (Journal of the College of Basic Education, 2023)
The current research aims to know the effect of roles playing method in achievement of physics subject for second –grade intermediate female students and theirs attitude towards physics. - To investigate from the aim of the research, researchers put the following two zero hypotheses: 1) There is no statistically significant difference at the level of (0.05) between the average scores of female students studying in a role-playing method and the average score for students who are studying the normal method in achievement test for physics subject.2) There is no statistically significant difference at the level of (0.05) between the average scores of female students studying in a role-playing method and the average score for students who are studying the normal method in attitude scales towards physics subject.-The experiment was implemented at the female students of second intermediate in Al-Tharyat Intermediate for female belonged to Education Directorate in Dyala Governorate and for the second term study (2010-2011).-Researchers adopted experimental design of two groups, the no. of female students of research sample about (51) from the second intermediate class of Al-Tharyat intermediate for female students belong to general directorate of Dyala Education / Al-Ghalis (2010/2011) distributed between two sections, Section (A) contained (26), Section (B) contained (25).- Section (A) was chosen randomly to represent control group which studied by normal method (followed method) , group (B) to represent experimental group which studied by the method of playing the roles.- The two groups have been equalization in the following variables (the female students achievement in physics subject for midyear, time age by months, intelligence).-A researchers built achievement test to measure the achievement two groups in physics subject after completion of his application of the experiment, consisted of (50),subjective items type multiple choice, and the number alternatives are four for each items measure the levels of remembrance , comprehension, application, and analysis.-To verify the of its content, by submitting it to a group of specialists, and then applied to the exploration sample to ensure the clarity of its items , and was sure of its stability by adoption equation Codrrichardson 20, and the reliability coefficient (0.83), also confirmed the distinctive powers of its items, the coefficient of difficulty, and effectiveness of alternatives.-And a researchers built attitude scale to measure the attitude of the female students towards physics subjects consist of (49) items distributed on three fields, to ensure the veracity of items by submitting it to a group of specialists, was then applied to the exploration sample to ensure the clarity of its items and have been found coefficient element by the equation of alpha Cronbach to (0.88).- The experimental applied in the second term of the academic year (2010-2011) and continued for (11) weeks, by two classes per week for each group, and the researcher taught the two groups by themselves. - The data treated statistically by adopting the (t-test) for two independent samples, and the equation Codrrichardson 20, and the equation Alpha Cronbach , the coefficient of difficulty, and distinguishing element. The results showed:1) There is a statistically significant difference between the scores of students of the experimental group which studied the method roles-playing and control group students who studied in the normal method in favor of the experimental group in testing achievement for Physics subject .2) there is no statistically significant difference between the scores of students of the experimental group which studied the method roles-playing and control group students who studied by normal method in the attitude scale towards the physics subject . - In light of the results of current research, the researchers recommended the adoption of playing roles method in the teaching of physics. And included in the decision of the curricula and teaching methods in colleges impartial. Researchers suggested making similar studies in several subjects, and the stages of a study to identify the impact in the achievement, and the attitude towards physics subject and other variables.